Structural valve degeneration: are there common mechanisms with atherosclerosis and calcific aortic stenosis? - A. E. Kostyunin (Вестник трансплантологии и искусственных органов)
Current research shows that some of the pathogenetic processes behind structural destruction of bioprosthetic valves are largely similar to those involved in the development of atherosclerotic vascular lesions and native valve calcification. These processes include lipid and leukocyte infiltration, typical for both prosthetic and native tissues. They are accompanied by formation of foam cells, excessive production of matrix-degrading enzymes and increased oxidative stress. This fact suggests that some approaches to conservative treatment of atherosclerosis may be useful for prolonging the lifespan of bioprosthetic valves.